Research issues of church architecture on the eastern borderlands of Poland - Pinkovskyi, Kostiantyn; Wrana, Jan (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2024)
The article analyzes the resource of church architecture and presents research methods that can be applied to the study of buildings in the eastern borderlands of Poland, focusing on Orthodox churches in the Lubusz Voivodeship. The aim of these methods is to assess their cultural, historical, and social value, as well as their role in shaping local identity. The result of applying these methods is the classification of existing and lost structures, an evaluation of their adaptive potential, and proposals for the protection of neglected buildings. The article emphasizes the need for research activities such as digitization, inventorying, and architectural analysis in order to organize data, support intercultural dialogue, and promote regional heritage.